Ntsikana : history and symbol studies in a process of religious change among Xhosa-speaking people - Hodgson, Janet (Department of Religious Studies, 2016)
The figure of Ntsikana, both as a man of history and as an historical symbol, is the focus of this study. I argue that change may come about by giving new meanings to old forms and images or by taking the new forms and content and filling them with the old, and that these two sets continue to exist side by side for a long time. Cumpsty's "Model of Religious Change in Socio-Cultural Disturbance" is used to identify the dynamics in the process and to explore the nature of the dialectic between innovation and assimilation of the new on the one hand, and continuity with the old on the other. The Ntsikana tradition is followed ever a period of two hundred years and well illustrates the need to see religious change as part of an ongoing process within a particular social and historical context.